Problem of amplification of the Jackson-type inequalities - Doronin , V. G.; Ligun , A.A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Inequalities strengthening certain inequalities of Jackson type are obtained with a precise constant.